Measurement of Ambient Concentration of NO2 In Obafemi Awolowo University Campus Using Passive Samplers - Onafeso, O.S.; Akeredolu, F.A.; Sonibare, J.A. (Ife Journal of Technology, 2010)
This study measured ambient concentration of NO2 in Obafemi Awolowo University (OAU) campus using locally fabricated passive samplers designed based on the principles of mass transfer and diffusion. Two types of samplers studied were tubes of varying lengths (2cm and 7cm) at three locations for different sampling durations. A mixture of sodium hydroxide (NaOH) and sodium iodide (NaI) in Methanol was used as absorbent for NO2. Samplers loaded with absorbents were exposed for durations of 1, 2, 3 and 4 weeks. Withdrawn samplers from sampling sites at the end of respective sampling periods were analysed in the laboratory using modified Griess-Saltzman method. Optical absorbance values of coloured solutions formed were measured with UV/VIS Spectrophotometer at 540nm. Results showed that the two sampler types were effective for sampling and both gave acceptable estimates in the 1 week sampling duration. The ambient air concentration of NO2 in Site 1 (7.0ppb-12.4ppb) is highest followed by Site 2 (4.2ppb-10.6ppb) and then Site 3 (0.2ppb-4.1ppb). All these values are below the limits set by the Federal Ministry of Environment which is 40ppb-60ppb.